Doc Martin. Last Christmas in Portwenn [videorecording (DVD)] - Ferguson, Craig, 1962-; Crowdy, Mark; Minghella, Dominic, 1967- (Acorn, 2023)
As Martin and James wait patiently to see Santa in his Grotto, Martin spots a medical concern that has him shut it down and send Santa packing-- until he's sure he isn't infectious. Louisa is determined not to let Martin ruin Christmas.